MENINGKATKAN KEMAMPUAN MEMBACA NYARING KALIMAT SEDERHANA PADA MATA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA KARTU KATA DI KELAS II SD NEGERI 2 LAKUDO - Masri Masri; Wa Ode Selfiyanti (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2021)
How to improve the ability to read simple sentences aloud in Indonesian subjects using word card media for grade II students of SD Negeri 2 Lakudo ?..The type of research used was classroom action research (PTK), which each cycle consisted of four stages, namely the planning stage. , action, observation and reflection. Data collection techniques used are quantitative data obtained through student learning outcomes tests and observation sheets. The results showed that the increase was seen from the number of students 16 people in the pre-cycle score, the number of students who achieved completeness was 5 people or 31.35%. In the first cycle who achieved completeness as many as 9 people or 56.25%. Whereas in the second cycle the number of students who achieved completeness was 13 people or 81.25% and the second cycle had reached the value according to the classical completeness target at 75%. The implementation of classroom action research using word card media in improving the ability to read aloud makes it easier for students to arrange letters into syllables and words and into simple sentences.